Marfan syndrome: insights from animal models - Jiang, Yuanyuan; Jia, Ping; Feng, Xiaoying; Zhang, Dingding (Frontiers in Genetics, 2025)
Marfan syndrome (MFS) is an inherited disorder that affects the connective tissues and mainly presents in the bones, eyes, and cardiovascular system, etc. Aortic pathology is the leading cause of death in patients with Marfan syndrome. The fibrillin-1 gene (FBN1) is a major gene involved in the pathogenesis of MFS. It has been shown that the aortic pathogenesis of MFS is associated with the imbalances of the transforming growth factor-beta (TGF-β) signaling pathway. However, the exact molecular mechanism of MFS is unclear. Animal models may partially mimic MFS and are vital to the study of MFS. Several species of animals have been used for MFS studies, including chicks, cattle, mice, pigs, zebrafishes, Caenorhabditis elegans, and rabbits. These models were developed spontaneously or in combination with genetic engineering techniques. This review is to describe the TGF-β signaling pathway in MFS and the potential application of animal models to provide new therapeutic strategies for patients with MFS.